2016
DOI: 10.1590/2317-1782/20162015109
|View full text |Cite
|
Sign up to set email alerts
|

Características da voz falada de idosas com prática de canto coral

Abstract: RESUMO Introdução Apesar dos vários estudos relacionados à voz na terceira idade e o canto, ainda são necessárias pesquisas que busquem entender os efeitos dessa prática na voz falada de idosos. Objetivo comparar as características da voz falada de idosas com prática de canto coral às de idosas sem essa vivência. Método fizeram parte deste estudo 75 idosas, sendo 50 com prática de canto coral que compuseram o grupo corista (GC) e 25 sem essa prática (GNC), que foram comparadas. Para caracterização das idosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(61 reference statements)
0
4
0
7
Order By: Relevance
“…Almost one third of the researched elderly (27.9%) reported that they participate or have participated in a choir. A study showed that elderly people who sing tend to perform physical exercises, because singing is motivating and stimulates the elderly to be more physically and socially active, which may influence their vocal quality (19) . Regarding the higher frequency of vocal alteration found among practicing singing participants, it can be explained by the fact that the elderly singing present a higher perception and appreciation of vocal symptoms (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Almost one third of the researched elderly (27.9%) reported that they participate or have participated in a choir. A study showed that elderly people who sing tend to perform physical exercises, because singing is motivating and stimulates the elderly to be more physically and socially active, which may influence their vocal quality (19) . Regarding the higher frequency of vocal alteration found among practicing singing participants, it can be explained by the fact that the elderly singing present a higher perception and appreciation of vocal symptoms (20) .…”
Section: Discussionmentioning
confidence: 99%
“…This aspect can be attributed to the practice of choral singing that would minimize the differences between younger and older elderly due auditory and vocal practice, guidelines related to caring for their voice, and the improvement in the individual's self-perception provided by musical training. 11 24 25 26 27 28 29 30 31 32 33 34 …”
Section: Discussionmentioning
confidence: 99%
“… 6 10 11 15 23 24 Among the activities considered for vocal training, singing is noteworthy, as it plays an important role in the promotion of vocal welfare. 11 24 25 26 27 28 29 30 31 32 33 34 …”
Section: Introductionmentioning
confidence: 99%
“…Isso pode se justificar porque a prática do canto motiva e encoraja idosos a serem mais ativos tanto no que diz respeito aos aspectos físicos, como sociais e isso pode contribuir na qualidade vocal (AQUINO et al, 2016), além de proporcionar uma importância social e afetiva (PRAZERES et al, 2013).…”
Section: Análise Críticaunclassified
“…Idosas foi a de que as idosas passaram a levar suas próprias garrafas de água para o encontro e referiam maior ingestão desse líquido após a inserção e participação no grupo. O canto coral pode auxiliar o desempenho vocal e deve ser um aliado aos profissionais da saúde na busca da promoção da saúde prevenção de distúrbios vocais (AQUINO et al, 2016).…”
Section: Uma Das Práticas De Bons Hábitos Observados No Grupo Saúde Vocal De Mulheresunclassified